Toward Understanding the Essence of Post-Translational Modifications for the Mycobacterium tuberculosis Immunoproteome - van Els, Cécile A. C. M.; Corbière, Véronique; Smits, Kaat; van Gaans-van den Brink, Jacqueline A. M.; Poelen, Martien C. M.; Mascart, Francoise; Meiring, Hugo D.; Locht, Camille (Frontiers in Immunology, 2014)
CD4+ T cells are prominent effector cells in controlling Mycobacterium tuberculosis (Mtb) infection but may also contribute to immunopathology. Studies probing the CD4+ T cell response from individuals latently infected with Mtb or patients with active tuberculosis using either small or proteome-wide antigen screens so far revealed a multi-antigenic, yet mostly invariable repertoire of immunogenic Mtb proteins. Recent developments in mass spectrometry-based proteomics have highlighted the occurrence of numerous types of post-translational modifications (PTM) in proteomes of prokaryotes, including Mtb. Well known PTMs in Mtb are glycosylation, lipidation or phosphorylation, known regulators of protein function or compartmentalization. Other PTM include methylation, acetylation and pupylation, involved in protein stability. While all PTM add variability to the Mtb proteome, relatively little is understood about their role in the anti-Mtb immune responses. Here, we review Mtb protein PTMs and methods to assess their role in protective immunity against Mtb.